A system implementation for analyzing and tracking motile objects in biomedical images - İlhan, Hamza Osman (My University, 2017)
Spermiogram is the first step of the infertility diagnosis. Computer Aided Sperm Analysis (CASA) and Visual Assessment (VA) are two evaluation techniques employed in spermiogram analyses. The VA is carried out by manually observing the sperm on counting chambers. Hence, analysis and diagnosis strongly depend on the skills and experiences of the observers. On the other hand, the CASA is a more advanced technology due to the improved computerized techniques and minimization of human intervention. However, it is more expensive than VA since it is an integrated computer based system and requires exhaustive parameter setting process. In this thesis, we aim to develop a combinational approach using the smartphone and computer for the sperm concentration and motility analysis. Smartphone was utilized to obtain images similar to the VA technique. The acquired samples were analyzed by using computerized methods to eliminate the observer variability. In this thesis, a software named as Computerized Sperm Counting and Trajectory Analyzing Software (CSCTAS) for automatically counting and tracking the sperm over one of the commonly using counting chamber, is proposed. Proposed software consists of seven modules executed sequentially: (1) Data Acquisition and Organization, (2) Automatic Grid and Region of Interest (ROI) detection and extraction, (3) Video Stabilization, (4) Motile/Immotile Spermatozoon Detection, (5) Spermatozoa Counting, (6) Motile spermatozoa tracking, and (7) Trajectory Classification. Each module consists of various combination of image processing techniques. Firstly, data acquisition and organization were performed using a novel approach to provide inexpensive design contrary to traditional CASA systems. Secondly, Region of Interest (ROI) extraction was realized by a combinational approach of line detection and segmentation methods. Then, feature matching based video stabilization was introduced to eliminate the vibrations occurred during the data acquisition step. In this respect, different descriptors were tested. The fourthly, Background and foreground extraction techniques were employed in immotile and motile spermatozoon detection process, respectively. Additionally, active contour, dual thresholding and clustering were implemented to enhance the segmentation of immotile spermatozoon in this step as well. Thereafter, detected sperms were counted by pixel based blob analysis. Motile spermatozoa were tracked by the Mean Shift and the Kalman Filters for the motility analysis. Various motility features were extracted from the trajectories to classify them into four classes. As the final step, results were reported to the users. Each module of the proposed software was individually tested. Two approaches of the automatic ROI detection and extraction steps were tested and compared on 80 videos of 20 subjects. Video stabilization idea was evaluated on 42 videos of 14 subjects. Two techniques were performed for the sperm concentration analysis. The performance of the Fuzzy C-Means based segmentation was measured on 15 videos of 5 subjects. A more advanced technique, dual thresholding and active contour based segmentation, was evaluated on 32 videos of 8 subjects. Finally, 32 videos of 8 subjects were used for the verification of the tracking technique. As a result, totally 201 semen videos obtained at different times from 55 subjects were included for the determination of the proposed spermiogram analysis approach. In the clinical research, we initially compared the counting results of CASA system, VA, and proposed CSCTAS with the proper concentration calculation. Normally, experts separately and manually count the motile and immotile spermatozoon within 16 and 10 squares to generalize the result as million per ml in the VA technique, respectively. According to the concentration analysis, proposed CSCTAS resulted in similar outputs as VA. It has less variation for immotile spermatozoa counting and is more efficient than the VA for the determination of specific diseases such as Asthenospermia. It is known that conventional SQA-Vision CASA is useless in the case of less than 5 million sperm cells. Therefore, presented approach is more efficient in the infertility diagnosis. In the motility analysis, CSCTAS gives the similar outputs when compared to SQA-Vision CASA. The SQA-Vision is more reliable technique when compared to VA in motility analysis because it is impossible to track single spermatozoa by eye for a period of time within other spermatozoa. Therefore the similarities between SQA-Vision and proposed CSCTAS is more meaningful than the comparison with VA technique for the motility analysis. According to the motility analysis results, CSCTAS is also efficient, cheaper and easier to use in labs for the motility analysis when compared to the conventional CASA systems. According to the obtained concentration and motility results, the proposed smartphone based sperm analysis can be adapted with the developed with the proposed CSCTAS in laboratories. Our proposed system stands out by its modularity, functionality, accuracy and low cost. Additionally, it eliminates the human factor in VA and CASA. Key words: Spermiogram, Makler Counting Chamber, Semen Analysis, Sperm Counting, Computer Aided Diagnosis Systems, Clinical Research

Sperm Sayımı infertilite teşhisinin ilk aşamasıdır. Bilgisayar Destekli Sperm Analizi (BDSA) ve Görsel Değerlendirme (GD) sperm analizlerinde kullanılan iki değerlendirme tekniğidir. GD, sayım çemberi üzerinden sperm gözlemleyerek gerçekleştirilir. Bu nedenle, teşhis genelde beceri ve deneyime bağlıdır. Öte yandan, BDSA, gelişmiş bilgisayar teknikleri ve insan etkilerinin izolesi sayesinde daha gelişmiş bir teknolojidir. Ancak, tümleşik bir sistem olduğundan GD tekniğinden daha pahalı bir analiz etme çözümüdür. Buna ek olarak, BDSA sistemlerinde, uğraştırıcı bir parametre belirleme işlemi gereklidir. Sistemin başarımı, belirtilen parametrelerle bağlantılıdır. Bu tez çalışmasında akıllı telefon ve bilgisayar kullanarak sperm konsantrasyonu ve motilite analizi için kombinasyonel bir yaklaşım geliştirmeyi amaçlıyoruz. Akıllı telefon, GD tekniğine benzer görüntüler elde etmek için kullanılmıştır. Sonrasında, insan etkilerini ortadan kaldırmak için bilgisayarla analiz yöntemleri kullanılarak numune analiz edilir. Çalışma kapsamında, sperm sayım çemberleri üzerinden elde edilen görüntüleri analiz etmek amacıyla Bilgisayar Destekli Sperm Sayma ve Hareket Analiz Yazılımı (BSSHAS) adlı bir yazılım önerildi. Yazılım, sıralı olarak koşturulan yedi modülden oluşmaktadır: (1) Veri Toplama ve Organizasyon, (2) Otomatik Izgara Tespiti ve İlgi Alanı çıkartma, (3) Video Sabitleme, (4) Hareketli / Hareketsiz Sperm Hücresi Algılama, (5) Spermlerin Sayımı, (6) Hareketli Sperm Takibi ve (7) Yörünge Sınıflandırması. Her adım, görüntü işleme tekniklerinden oluşan çeşitli kombinasyondan oluşur. Öncelikle, veri toplama ve organizasyonu, geleneksel BDSA sistemlerinin aksine, daha az maliyetli bir tasarım sağlamak için yeni bir yaklaşım kullanılarak gerçekleştirildi. Sonrasında, yazılım tarafında, İlgi Alanları (İA) çıkarma işlemi, çizgi algılama ve bölütleme yöntemlerinin kombinasyonel bir yaklaşımı ile gerçekleştirildi. Ardından, veri toplama aşamasında oluşan titreşimleri ortadan kaldırmak için özellik eşleme tabanlı video sabitlemesi üzerine algoritma geliştirildi. Özelliklerin çıkartılması anlamında, farklı tanımlayıcılar test edildi. Dördüncü olarak, hareketsiz ve hareketli sperm hücresinin algılamasında sırasıyla arka plan ve ön plan çıkartma teknikleri kullanıldı. Ek olarak, bu aşamada hareketsiz sperm bölütleme başarımını arttırmak için aktif kontur, çift eşikleme ve kümeleme yöntemleri uygulandı. Bundan sonra tespit edilen spermler piksel tabanlı blob analizi ile sayıldı. Hareketlilik analizi için hareketli olarak tespit edilen spermler, Mean Shift ve Kalman Filtreleri ile takip edildi. Yörüngelerden çeşitli hareket özellikleri çıkarılarak dört sınıfa ayrıldı. Son adım olarak, sonuçlar kullanıcılara bildirildi. Önerilen yazılımın her modülü ayrı ayrı test edildi. Otomatik İA saptama ve çıkartma adımında, iki yaklaşım incelendi ve 20 hastadan elde edilen 80 video üzerinden denendi. Sonuçlar karşılaştırıldı. Video sabitleme çalışması, 14 hastadan elde edilen 42 video üzerinde değerlendirildi. Sperm konsantrasyon analizi için iki teknik test edildi. Fuzzy C-Means tabanlı bölümlemenin performansı 5 denekten elde edilen 15 video üzerinde ölçüldü. Daha gelişmiş bir teknik, çift eşikleme ve aktif kontur tabanlı bölütleme, 8 deneğin 32 videosunda değerlendirildi. Son olarak, 8 hastadan elde edilen 32 video, izleme tekniğinin doğrulanması için kullanıldı. Sonuç olarak, önerilen spermiogram analiz yaklaşımının test aşamasına, 55 denekten farklı zamanlarda elde edilen toplam 201 semen videosu dahil edilmiştir. Klinik araştırmada, başlangıç olarak BDSA sistemi, GA ve önerilen BSSHAS sperm konsantrasyon sayım sonuçlarını uygun yoğunluk hesaplama tekniği kullanarak karşılaştırdık. GA tekniğinde, uzmanlar manuel olarak hareketli ve hareketsiz spermleri 10 ve 16 kare genellemesini kullanarak saymaktadırlar. Konsantrasyon analiz sonuçlarına göre, önerilen BSSHAS, GA ile benzer çıktılar üretmiştir. Önerilen yöntem, hareketsiz spermlerin sayımında daha tutarlı ve az dalgalanma göstermektedir. Ayrıca, Astenospermi gibi spesifik hastalıkların belirlenmesi için GA'den daha etkilidir. Geleneksel SQA-Vision BDSA sisteminin ise 5 milyondan az sperm hücresi bulunan örneklerde analiz yapamayacağı bilinmektedir. Bu nedenle, sunulan yaklaşım, kısırlık tanısında daha etkilidir. Hareketli sperm analizinde ise, önerilen BSSHAS, SQA-Vision CASA ile karşılaştırıldığında benzer çıktılar vermektedir. Tek bir spermatozoanın diğer spermler içerisinde bir süre boyunca manuel olarak gözle izlenmesinin güç olmasından dolayı, SQA-Vision, hareketli hücre sayımı analizinde, GA tekniğine göre daha güvenilir bir tekniktir. Dolayısıyla, SQA-Vision ile önerilen BSSHAS arasındaki benzerlikler, hareketlilik analizi için GA tekniği ile karşılaştırmadan daha anlamlıdır. Elde edilen konsantrasyon ve hareket analizi sonuçlarına göre, önerilen akıllı telefon temelli sperm analiz yaklaşımı laboratuvarlarda uygulanabileceği kanıtlanmaktadır. Önerilen sistemimiz modülerlik, işlevsellik, doğruluk ve düşük maliyet ile dikkat çekmektedir. Buna ek
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2017
Keywords: Spermiogram; Makler Counting Chamber; Semen Analysis; Spermiogram; Makler Sayma Çemberi; Sperm Analizi; Sperm Sayımı; Bilgisayar Destekli Tanı Sistemleri; Klinik Araştırma